The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/jcmm.17701
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of ferroptosis in obesity

Abstract: Obesity is widely recognized as a major global health problem caused by a chronic energy imbalance resulting from a combination of excess caloric intake and insufficient energy expenditure. Excessive energy intake and physical inactivity are traditional risk factors for obesity. Obesity is a risk factor for many diseases, including hypertension, diabetes and tumours. Recent studies have found a strong link between ferroptosis and obesity. Ferroptosis is an iron‐dependent regulated cell death caused by iron ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…42,43 VASH-1 binds to receptors on renal mesangial cells and reduces urinary protein production by activating the NK-κB pathway, whereas VASH-1 consumes large amounts of secreted proteins to reduce proteinuria. [44][45][46] Therefore, the level of VASH-1 in DN patients with massive proteinuria will be significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 VASH-1 binds to receptors on renal mesangial cells and reduces urinary protein production by activating the NK-κB pathway, whereas VASH-1 consumes large amounts of secreted proteins to reduce proteinuria. [44][45][46] Therefore, the level of VASH-1 in DN patients with massive proteinuria will be significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Related diseases modifiable by ferroptosis was reviewed in details. 9 In particular, ferroptosis is involved in the pathological process of PE. Study found that ferroptosis in trophoblasts via the ferritinophagy pathway implicated in the pathogenesis of PE.…”
Section: Ferrop Tos Is and Pementioning
confidence: 99%
“…So far, ferroptosis has been found in many diseases and plays an important role in the occurrence and development of many diseases. Related diseases modifiable by ferroptosis was reviewed in details 9 …”
Section: Ferroptosis and Pementioning
confidence: 99%
“…In addition, further studies are needed to investigate the specific involvement of ferroptosis in T2DM. The previous review summarized that vitamin D might modulate the ferroptosis signaling pathway [29][30][31][32]. Therefore, vitamin D may play a vital role in alleviating T2DM by modulating the ferroptosis signaling pathway.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%